Maternal COVID-19 vaccination status and association with neonatal congenital anomalies - Santos, Janelle; Miller, Megan; Branda, Megan E.; Mehta, Ramila A.; Theiler, Regan N. (Frontiers in Pediatrics, 2024)
Introduction: Despite recommendations for COVID-19 vaccination in pregnant people, the effect of vaccination on neonatal outcomes remains unknown. We sought to determine the association between COVID-19 vaccination status in pregnancy and presence of neonatally diagnosed congenital anomalies.Methods: A comprehensive vaccine registry was combined with a delivery database to create a cohort including all patients aged 16-55 years with a delivery event between December 10, 2020 and December 31, 2021 at a hospital within the Mayo Clinic Health System. Pregnancy and neonatal outcomes were analyzed in relation to vaccination status and timing, including a composite measure of congenital anomalies diagnosed in neonatal life. Comparisons between cohorts were conducted using chi-square test for categorical and Kruskal Wallis test for continuous variables. A multivariable logistic regression was modeled to assess the association with congenital anomalies.Results: 5096 mother-infant pairs were analyzed. A total of 1,158 were vaccinated, with 314 vaccinated in the first trimester. COVID-19 vaccination status, including vaccination during the first trimester of pregnancy, was not associated with an increased risk of composite congenital anomalies. When further examining congenital anomalies by organ system, we did demonstrate a significant difference in eye, ear, face, neck anomalies between vaccinated and not vaccinated groups (Table 3, Not vaccinated= 2.3%, Vaccinated= 3.3%, p-value 0.04) however we did not demonstrate this difference between the 1 st trimester and not vaccinated groups (Table 3, Not vaccinated= 2.3%, 1 st Trimester= 2.5%, p-value 0.77). No differences were found between not vaccinated, vaccinated, or 1 st trimester vaccinated groups for any other organ systems. There were no differences in birthweight by gestational age, APGAR scores, incidence of NICU admission, or living status of the neonate by vaccination status.We add additional information regarding the safety of COVID-19 vaccination status and timing as it pertains to neonatal composite congenital anomalies, with no association demonstrated. Our findings agree with prior literature that COVID-19 vaccination is not associated with adverse pregnancy outcomes or small for gestational age neonates. Further research is needed to elucidate the association between COVID-19 vaccination and eye, ear, face, neck, anomalies.